Six sick sheep 101 tongue twisters - Cole, Joanna; Calmenson, Stephanie; Tiegreen, Alan (New York : Beech Tree Paperback Books, 1993)
A collection of all kinds of tongue twisters: some only two or three words long, some that tell a story, and some featuring a theme.
Keywords: Riddles, Juvenile; Tongue twisters